LIMITED JOINT MOBILITY SYNDROME IN DIABETES MELLITUS - T. S. Panevin; L. I. Alekseeva; G. A. Melnichenko (Научно-практическая ревматология)
Patients with diabetes mellitus (DM) often show changes in the locomotor apparatus (LMA), in particular cheiroarthropathy, a specific lesion of the connective tissue structures of the hand in the presence of persistent hyperglycemia, which leads to limited joint mobility (LJM) generally in the absence of pain syndrome. Some authors use the term «LJM syndrome» to describe LMA lesion in DM, since in the long course of the disease, the small and large joints of not only the upper, but also the lower limbs are involved in the pathological process. LJM is one of the little studied and poorly diagnosed conditions in comparison with traditional micro- and macro-vascular complications of DM, which, due to their direct correlation with life expectancy, receive more attention. The LJM syndrome is associated with other late complications of DM and can significantly impair functional activity, self-care, and quality of life. Damages to periarticular tissue and joints in DM are believed to be caused by the accumulation of glycation end products. A clinical examination plays a key role in the diagnosis of cheiroarthropathy.